Dosis de gallinaza y su influencia en componentes agronómicos y rendimiento de Origanum vulgare L., orégano hoja ancha, en Zungarococha - Loreto. 2022 - Ojanama Vasquez, Eddy Martin (2022)
The thesis "Dose of gallinaza and its influence on the agronomic components and yield of origanum vulgare L., broadleaf oregano, in Zungarococha-Loreto. 2022" was located in Zungarococha, south of the city of Iquitos. The objective of the study was to verify the influence of gallinaza doses on the agronomic components and yield of Origanum vulgare L., broadleaf oregano, whose treatments were: 10, 20, 30 and 40 t / ha, operating the Experimental Design of Completely Random Blocks and the Tukey Comparison Test. The variables evaluated were: Height and diameter of the plant, number of branches, number of leaves and weight of leaves / plant and weight of leaves / ha, obtaining the following conclusions: mediated the agronomic behavior and yield of the crop of Origanum vulgare L., broadleaf oregano; the T4 Treatment (40 t of chicken/ha), demonstrated the best agronomic and crop yield behavior; it also presented the best weight yield of sheets / ha, with 19,440 t / ha, obtaining a profit of S / .80,964.00